Comparing the impact of high pressure, pulsed electric field and thermal pasteurization on quality attributes of cloudy apple juice using targeted and untargeted analyses. (June 2019) - Wibowo, Scheling; Essel, Esther Aba; De Man, Sofie; Bernaert, Nathalie; Van Droogenbroeck, Bart; Grauwet, Tara; Van Loey, Ann; Hendrickx, Marc
Abstract: The impact of low-oxygen spiral-filter press technology combined with thermal pasteurization (TP), pulsed electric field (PEF) and high pressure processing (HPP) on cloudy apple juice quality was investigated immediately after the treatments and after 3 weeks of storage at 4 °C. Based on equivalent levels of microbial safety and desired shelf-life, low and high processing intensities were selected: TP (72 °C/15 s; 85 °C/30 s), PEF (12.5 kV/cm, 76.4 kJ/L; 12.3 kV/cm, 132.5 kJ/L), and HPP (400 MPa/3 min; 600 MPa/3 min). High intensity thermal treatment resulted in a bright, yellowish color which was maintained during storage. PPO and POD activities were largely reduced by high intensity PEF and TP yet showed high resistance to HPP. The highest vitamin C content was provided by fresh juice followed by PEF-treated juices. Due to oxidative degradation reactions, vitamin C of all treated samples significantly decreased during storage. Immediately after processing, high cloud stability values were obtained in all samples; however, cloud stability decreased during storage particularly for HPP juices with high residual PME. No significant changes were observed in pH, titratable acidity, organic acid and sugar content which also corresponded to sweet and sour taste. Results from untargeted volatile profiles showed that esters increased after PEF and were better retained after HPP. Contrary to TP treatment where ester degradation reactions occurred together with the formation of off-flavors. Most of the volatiles decreased during storage which could be linked to oxidation and ester hydrolysis reactions. Industrial relevance: Being one of the most popular fruit juices consumed worldwide, cloudy apple juice can still undergo quality changes such as color degradation, cloud loss (fast sedimentation) and flavor changes during processing and storage. This study evaluates the potential of low-oxygen spiral-filter press in combination with different preservation technologies to obtain a maximal quality of cloudy apple juice. Results showed that high intensity thermal pasteurization can effectively inactivate quality-degrading enzymes, therefore it is useful to obtain an optimal cloudy apple juice product in terms of color and cloud stability. Although HPP has minimal impact on aroma of the juice, shelf-life of the juice may be limited due to incomplete enzyme inactivation. In the case of PEF treatment, thermal effects may contribute to maintain apple juice quality. Highlights: Enzymes can be completely inactivated by high intensity thermal processing. Less effect of processing and storage on particle sizes, acidity and sugar content Spiral-filter press combined with PEF or HPP retained the fresh apple juice aroma. Spiral-filter press coupled with severe pasteurization preserved color and cloud stability. Thermal effects resulting from PEF may contribute in maintaining the juice quality.